Enhancing thermal conductivity and near-infrared radiation reflectance of poly(ε-caprolactone)/poly(lactic acid)-based nanocomposites by incorporating hexagonal boron nitride - Decol M.* (2019)
© 2019 Society of Plastics EngineersThis work aims to develop multifunctional biodegradable ternary nanocomposites with heat dissipation capability. The effects of adding hexagonal boron nitride (hBN), regarding phase morphology, near-infrared radiation (NIR) reflectance and thermal conductivity of poly(ε-caprolactone) (PCL) and poly(lactic acid) (PLA) blends were investigated. The hBN nanoparticles were selectively localized in the PCL phase. Scanning electron microscopy showed that the increased hBN concentration in the PCL/PLA blend led to a more fibrillar PLA phase and, after compression molding, its morphology presented a co-continuous structure. Adding hBN nanoplatelets increased the reflectance in the NIR region by 184%, the thermal conductivity of the PCL/PLA by 400%, and increased the blend's thermal stability. The co-continuous morphology could favor the heat flow, because it promotes the confinement of the hBN nanoplatelets in the PCL phase, favoring the conductive thermal pathway formation. POLYM. COMPOS., 40:3464–3471, 2019. © 2019 Society of Plastics Engineers.